2014
DOI: 10.2118/164993-pa
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality for Training and Decision Making: Preliminary Results of Experiments Performed With a Plant Simulator

Abstract: The use of immersive virtual reality (IVR) for training is an idea that has existed for a long time; the real, unclarified doubt about its use is whether it does really increase performance with respect to traditional methods such as classroom and on-the-job training. The most critical point of traditional training methods is the difficulty to train operators about a system's deviations from nominal conditions. But even the more-advanced simulation-supported training approach, commercially represented by the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…For operation and maintenance training, it is observed that the immersive virtual reality (IVR) which deployed the 3D plant model was proposed to enable the control-room operator (CROP) and field operator (FOP) to be trained simultaneously. Besides, the IVR enables the performance to be assessed by eliminating the subjectivity and the trainees were trained under an experimental approach instead of classical approach (Colombo et al, 2014). For disaster planning, a 3D visualisation model was integrated with other advanced technologies to monitor and forecast the disaster.…”
Section: Production Maintain and Operatementioning
confidence: 99%
“…For operation and maintenance training, it is observed that the immersive virtual reality (IVR) which deployed the 3D plant model was proposed to enable the control-room operator (CROP) and field operator (FOP) to be trained simultaneously. Besides, the IVR enables the performance to be assessed by eliminating the subjectivity and the trainees were trained under an experimental approach instead of classical approach (Colombo et al, 2014). For disaster planning, a 3D visualisation model was integrated with other advanced technologies to monitor and forecast the disaster.…”
Section: Production Maintain and Operatementioning
confidence: 99%
“…Detailed guidelines of building realistic VR applications have been a subject of numerous research in previous years [1,2,5,6,19,24,29] and are beyond the scope of this paper. Only the most important stages of the process from the viewpoint of the knowledge-based approach -2 and 3 -will be mentioned here.…”
Section: Implementation and Applicationmentioning
confidence: 99%
“…Nowadays VR is mostly used in engineering -for extended, CAD-based virtual design [4,5], industrial training [6,7], simulation of machine operation or manufacturing processes [8] and many other applications. One of the industry branches using the VR benefits to a great degree is the automotive branch [9].…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, the demands by the operators were more physical than mental and manual intervention of physical devices was sufficient for continuous and safe production. A number of recent studies highlighted the benefits of operator training and its correlation with decrease in accidents and abnormal situations . The work of Kluge et al .…”
Section: Introductionmentioning
confidence: 99%